Review Of SIMRS Implementation In RSUD Dr. Pirngadi, Medan City - Maulana, Fajar; Halawa, Luk Juni S (SEAN Institute, 2023)
PERMENKES No. 82 of 2013 Articles 3 and 4 state that hospitals are obliged to carry out SIMRS and every hospital must carry out management and development of SIMRS. The purpose of this study was to find out how the obstacles in the implementation of SIMRS in RSUD Dr. Pirngadi Medan City. This study uses descriptive qualitative research with a retrospective approach where data collection is carried out by interviewing from June to September 2022 to the head of the ICT installation at Dr. RSUD. Pirngadi Medan City. Based on the research that in the implementation of SIMRS in RSUD Dr. Pirngadi Medan City experienced obstacles, namely man (lack of human resource knowledge), mechinness (network that sometimes errors) and money (money). The conclusion is RSUD Dr. Pirngadi Medan City in implementing SIMRS is still experiencing obstacles that interfere with officers in carrying out. Based on this, it is suggested to the hospital to continue to conduct training and socialization to employees regarding the understanding and use of information systems and to find sufficient sources of funds to overcome the implementation of SIMRS in RSUD Dr. Pirngadi City and the existence of a special team to handle the occurrence of network errors